2010
DOI: 10.1364/ol.35.003321
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-trap laser tweezers Raman spectroscopy for simultaneous monitoring of the biological dynamics of multiple individual cells

Abstract: We report the development of a multiple-trap laser tweezers Raman spectroscopy (LTRS) array for simultaneously acquiring Raman spectra of individual cells in physiological environments. This LTRS-array technique was also combined with phase contrast and fluorescence microscopy, allowing measurement of Raman spectra, refractility, and fluorescence images of individual cells with a temporal resolution of ~5 s. As a demonstration, we used this technique to monitor multiple Bacillus cereus spores germinating in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…In the results described above, the Raman analysis was performed with the simplest configuration in that the same laser beam was used as optical tweezers and simultaneously as excitation source for Raman scattering. However, different experimental schemes could be set up, and improve in the future, the quality of interpretation of the biological alterations observed either in pathological conditions or upon treatment [40][41][42][43][44]. In more advanced configurations, dual wavelength optical tweezers could be coupled to confocal Raman microscopes; when one of the beams excites the Raman spectrum, a second beam for tweezing enables manipulation of the environment of the trapped objects, for example, a single living cell.…”
Section: Discussionmentioning
confidence: 99%
“…In the results described above, the Raman analysis was performed with the simplest configuration in that the same laser beam was used as optical tweezers and simultaneously as excitation source for Raman scattering. However, different experimental schemes could be set up, and improve in the future, the quality of interpretation of the biological alterations observed either in pathological conditions or upon treatment [40][41][42][43][44]. In more advanced configurations, dual wavelength optical tweezers could be coupled to confocal Raman microscopes; when one of the beams excites the Raman spectrum, a second beam for tweezing enables manipulation of the environment of the trapped objects, for example, a single living cell.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of strong absorption, cells may withstand these exposures. [14][15][16] In one example, germinating bacterial spores held in a 4 mW laser trap were studied by Raman spectroscopy, showing that the trapped spores exhibit heterogeneous germination times, but are otherwise unaffected by the trap after 90 min of continuous laser exposure. 16 However, several groups have reported that optical trapping strongly affects red blood cells (RBCs), due to the presence of strongly absorbing hemoglobin.…”
mentioning
confidence: 99%
“…[14][15][16] In one example, germinating bacterial spores held in a 4 mW laser trap were studied by Raman spectroscopy, showing that the trapped spores exhibit heterogeneous germination times, but are otherwise unaffected by the trap after 90 min of continuous laser exposure. 16 However, several groups have reported that optical trapping strongly affects red blood cells (RBCs), due to the presence of strongly absorbing hemoglobin. 3,6,8,11,12 Some of these effects can be useful for monitoring cell function, as Liu et al have used laser-tweezers Raman spectroscopy to show that red blood cells reversibly deoxygenate when exposed to the forces within an optical trap, 11 and that the ability of cells to respond to optical forces can be used as a functional test for red blood cells.…”
mentioning
confidence: 99%
“…Ye and Zhang designed a LTRS system equipped with two lasers (an infrared laser and a visible laser) for trapping and Raman excitation, respectively [80]. In addition, a multiple-trap LTRS array for simultaneously acquiring the Raman spectra of several cells was developed, which markedly improved the work efficiency of LTRS [81,82]. Besides, tip-enhanced Raman spectroscopy, the combination of AFM with Raman spectroscopy, was successfully used to study the membrane surface chemistry of a single living cell with ultra-high morphology/spectroscopy spatial resolution (less than 10 nm) [83,84].…”
Section: Complementary Assets Of These Three Techniquesmentioning
confidence: 99%